Preferensi Laki-Laki Dan Perempuan Dalam Memilih Fasilitas Pelayanan Kesehatan Pada Pasien Di Puskesmas Kassi-Kassi - Mauliadi Ramli . (Universitas Negeri Makassar, 2022)
AbstractMauliadi Ramli, 2021. This study aims to find out. To find out what factors are related to the preferences of male and female patients in choosing health care facilities at the Kassi-Kassi Public Health Center Makassar. This study took a qualitative descriptive type of research and used a qualitative approach. sociology. In selecting informants, the technique used was purposive sampling through determining criteria, namely people who had been or were patients at Kassi Kassi Health Center Makassar City. Data collection techniques used are observation, interviews, and documentation. And the data analysis technique used is data reduction, data presentation, and drawing conclusions. Based on the results of the study, it can be concluded that the results of this study are factors related to patient preferences in choosing health care facilities, consisting of personality factors, supporting factors, and the needs of male and female patients themselves. Keywords: Preference, Sociology of Health, Healthy lifestyle, Health.